O projeto de crítica da ideologia de Slavoj Zizek - Campos, Philippe Augusto Carvalho (2021)
The subject-matter of ideology critic has its genesis in Marx and Engels. In a second moment of the theme we find Frankfurt School. The resurgence of the subject is now seen in the work of Slovenian philosopher Slavoj Zizek. Based on Peter Sloterdijk diagnosis the we live in a post-ideological time, Zizek recover the critic of ideology by using Lacanian psychoanalysis and a re-reading of Hegelian philosophy to return to the Marxist theme. In this work we trace the general lines of how the author builds his project, based on aspects of the Frankfurt School, Althusser's conception of ideology, Sohn-Rethel's concept of real abstraction and the ideological theater of 20th century totalitarianisms. From there, we turn to the way Zizek elaborates the concept of ideology, since the construction of his object and the concept of fantasy, both derived from Lacanian psychoanalysis. That done, we move on properly to the concept of critic of ideology, for that, we focus on the way in which the author conceives the subject, derived from Hegel and, also, from Lacanian psychoanalysis.